Instructor’s and Students’ Perspectives on Hyflex Learning: A Collaborative Self-Study - Song, Liyan; Bailey, Emily; Siff, Brocha; Boyd, Tracy; Boettinger, Jeremy; Santi, Lauren; Neimeyer, Lauren K.; Oladipo, Tolulope (The Canadian Journal of Action Research, 2024)
The paper reports a collaborative self-study on instructor’s and students’ experiences in a HyFlex course in a higher education institution. The COVID-19 pandemic acted as a catalyst for the resurgence of multi-modal course delivery such as HyFlex instruction in higher education settings. The reported collaborative self-study aimed to examine both the instructor’s and the student’s perspectives on HyFlex learning. One instructor and seven students in a HyFlex class participated in the study through shared individual and collaborative reflections on their experiences. The findings indicated the benefits, potential, and challenges of HyFlex learning and instruction.